The role of the sound effect to represent the psychopathic character in cinema (Al-Academy, 2023)
The process of employing modern technology in a consistent manner is what the researcher is interested in, and the psychological role of the sound effect in enhancing psychopathic representations in cinematic characters, which had a wide resonance in the field of cinematic films, and after the predominance of digital technology in the production of contemporary films, the sound effect has a higher efficiency And a good level of advanced aesthetic and dramatic expression in film employment, so many directors resorted to this type of films by using various new and advanced techniques and technological programs in their industry, since the traditional construction does not achieve the dazzling that the viewer desires.Accordingly, the researcher found that it is necessary to shed light on this topic due to its importance and research in it, so a title was chosen for it (the role of the sound effect to represent the psychopathic personality in the cinema), to include the methodological framework, defining the problem, its importance and the need for it, and defining the terms (sound effect, personality Psychopathy), and the theoretical framework included the first topic (the sound effect’s significance and concept),the second topic (the psychological dimension of the psychopathic personality in the cinema), and the third topic (the psychopathic personality from the sound semantics in the cinema), after that the researcher came out with a set of indicators that he adopted as tools for analyzing the sample And the framework concluded with previous studies.The analytical descriptive approach took its approach, and an intentional sample that meets the research objectives, the American movie (Schizophrenia SPILT), directed by M. Night Shyamalan, produced in 2016, and the researcher relied on the indicators provided for the theoretical framework to analyze the sample, and took the scene as a main analysis unit in the research, and it was produced the study a number of results and conclusions, then conclude the research with a list of sources and appendices